A política de governança pública aplicada aos processos seletivos de pós-graduação da UFPB - Souza, Rosandro Barros da Silva (2020)
This present research examines how public governance politics can be applied to the selection processes for admission, master's and doctoral degrees, at UFPB PostGraduate Programs, in order to allow advances in terms of management, compliance, standards and ethics at the university. This proposal signals an attempt to solve problems related to university management based on Decree Nº. 9,203, of 2017, which displays information on the Governance Policy of the Federal Public Administration. Thus, the theoretical framework is based on the guidelines of public tenders for the Democratic State of Law and on the concepts of Public Governance within the scope of Federal Universities in Brazil. In effect, this research includes a qualitative approach of documentary and applied nature. An analysis of the data indicates that, in general, the selection processes at UFPB demonstrate progress in the public governance structure, in its systematics still in compliance with standardization, simplification and definition of rules, in addition to stimulating senior management to incorporate a management culture based on the public interest as a pedagogical tool. Thus, it was possible to conclude that many of the questions faced by UFPB in the context of Selective Postgraduate Program Processes could be avoided with the effective implementation of the public governance policy described in Decree nº 9.203, notably when together with improvements in aspects such as risk management, compliance, debureaucratization and regulatory improvement.